A performance de Rosa Passos na canção popular brasileira - Villar, Maria Gabriella Cavalcanti (2019)
This dissertation is the result of a research that I developed on the performer and composer, Rosa Passos, and aimed to understand and identify musical aspects that represent her performance in the Brazilian popular song, trying to understand how it is characterized. For this, I analyzed three songs recorded by Rosa Passos: Águas de Março - Tom Jobim from CD Eu e meu coração (2003, Velas); A Ilha – Djavan of the TVE Spain audiovisual presentation, held at the 32nd Vitoria Jazz Festival - Gasteiz, Spain (2008); Dunas - Rosa Passos/Fernando de Oliveira from the CD Som de Casa (Paulo Paulelli/2018) under the following parameters: metric, agogic (rhythmic division - accentuations, anticipations, accelerations, delays, pauses). Intervals (jumps) in the melody, relationship of the whole with the parts - distribution of the notes, dynamics, breathing, timbres, gestures and vocal resources. To observe, to identify through aural analyzes the resources/musical aspects and interpretative used by Rosa Passos in their performances recorded in CD and audio-visual, focusing on their specificities, idiosyncrasies and sociohistorical-cultural contexto. Analyze the relationship between voice and guitar, voice and band in CD and audiovisual recordings. To investigate which elements in their performance repeat themselves as a vocal pattern. The methodology was based on the aural analysis of the phonogram and to describe it, I tried to use a language that aliases musical terms with a more empirical description of the performance, as Rosa Passos herself does when talking about her musical performances. Besides the analyzes, I conducted interviews with Rosa Passos, her musicians and producer, as well as I went to the field to follow her performance in recording studio and stage. The results were obtained through all this process of data collection, from my perception as a singer, teacher of popular song and researcher, as well as Rosa Passos' great availability to this research. These point to a musical performance that is driven by creativity. Rosa Passos is an artist of creation, whether as a vocal interpreter, instrumental or as a composer.